Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Toko Mida Top Di Demak - Khanifah, Hanik; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The purpose of this analysis is to investigate how the level of customer satisfaction at the Mida Top Demak store relates to service quality. In this analysis, a representative data collection technique involving distributing questionnaires and a sample of 32 people was used. This analysis is processed through descriptive quantification method. T test, F test and simple linear regression are needed to analyze the data. The SPSS version used for data management is 29.0. The T test proves that service quality has a positive impact on customer satisfaction, and the F test proves that customer satisfaction is positively influenced by service quality. The findings of this study prove that service quality at Toko Mida Top Demak has a very positive impact on customer pleasure/satisfaction.